Children's Social Representations of English Teaching and Learning: A Study in Medellín, Colombia - Isabel Cristina Cadavid-Múnera (Universidad Nacional de Colombia, 2022)
This article reports the findings of a qualitative interpretive research study that explored the social representations children have about the teaching and learning of English as a foreign language in elementary schools in Medellín, Colombia. Sixty children in first, third, and fifth grades of public and private schools participated in the study. Techniques such as drawings, pretend play, conversations, and semi-structured interviews were used to collect data. Three analogies summarize children's perceptions in this study: learning as "echo," teaching as a power instrument, and English as a tool to "survive" or to "live and interact with others." Finally, a reflection and some implications for the teaching of English to children are presented.